Pengaruh Promosi Online Terhadap Perilaku Konsumtif Generasi Z di Market place - Paulino Da Costa Ferreira; Hwihanus Hwihanus (Universitas Kristen Indonesia Toraja, 2025)
This study aims to explore the impact of online promotion on the consumptive behavior of Generation Z in the marketplace. The main focus of the research is on forms of promotion such as discounts, flash sales, and influencer endorsements, as well as how these factors influence shopping decisions. Using quantitative methods, data was collected through a survey of 200 respondents aged 18-24 years. Data analysis was carried out using SPSS, involving correlation and regression tests. The results show that online promotions have a significant impact on the consumptive behavior of Generation Z, with discounts as the dominant factor. The study recommends businesses to maximize their online promotion strategies to increase traction and sales.